2020
DOI: 10.12669/pjms.36.3.1558
|View full text |Cite
|
Sign up to set email alerts
|

The impact of post PCNL tube type on blood loss and postoperative pain

Abstract: Objective: To evaluate the impact of nephrostomy tube type on postoperative pain and blood loss following percutaneous nephrolithotomy (PCNL). Methods: This is a prospective non-randomized study performed at Aga Khan University Hospital from July 2017 to June 2018. In this study we prospectively studied adult patients (16 to 65 years) who underwent unilateral PCNL. Patients who had nephrostomy with balloon (12Fr Foley’s catheter) were compared with patients who had nephrostomy without balloon (12Fr Nelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…Another study by Yarimoglu et al [15] showed no significant association between the STONE score and EBL. The mean hemoglobin drop was 1.15 ±0.92 in our study, which is similar to a recent study by Jamil et al [12] comparing Foley and Nelaton™ catheter nephrostomy tubes. However, they noted no significant difference in the mean hemoglobin drop in the two groups with balloon versus non-balloon catheter nephrostomy respectively (1.08 ±0.7 and 1.14 ±0.69).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Another study by Yarimoglu et al [15] showed no significant association between the STONE score and EBL. The mean hemoglobin drop was 1.15 ±0.92 in our study, which is similar to a recent study by Jamil et al [12] comparing Foley and Nelaton™ catheter nephrostomy tubes. However, they noted no significant difference in the mean hemoglobin drop in the two groups with balloon versus non-balloon catheter nephrostomy respectively (1.08 ±0.7 and 1.14 ±0.69).…”
Section: Discussionsupporting
confidence: 92%
“…Mostly it is mild and self-limiting, however, occasionally it could be life-threatening. Ultrasound-guided access [10], miniaturization of the instruments [11], use of the balloon catheter nephrostomy tube [12], and tubeless PCNL with the use of tract sealant [13] are some of the ways described to minimize bleeding complications. Various patient and stone-related factors have also been studied to predict PCNL complications including previous interventions [14].…”
Section: Discussionmentioning
confidence: 99%
“…The key critical and difficult point of a PCNL operation is creating the channel for percutaneous nephrolithotomy. The risk of the operation and the rate of calculus clearance are strongly related to the selection and establishment of the percutaneous renal puncture route 15 , 16 . Therefore, it a critical point in PCNL surgery has become to clarifying the relationship between the structure of the renal collection system, the distribution of blood vessels and the position of the calculus, to rationally plan the preoperative puncture of the renal calyx and to optimize the operation the steps of the lithotripsy operation.…”
Section: Discussionmentioning
confidence: 99%
“…Jamil et al reported that use of nephrostomy tube with balloon, such as Foley catheter, after PCNL as this is associated with less hemoglobin drop as compare to nephrostomy tube without balloon. 16 We routinely used a 16F nephrostomy tube without balloon for this purpose. Some antibiotics are known to have caused hemorrhage.…”
Section: Discussionmentioning
confidence: 99%